The expiration in the sanctioning procedure in Peru - Alejos Guzmán, Oscar (2020)
The expiration is a new legal institution in the Peruvian sanctioning procedure. Its incorporation in the Administrative Procedure Act occurred with the modifications made by the Legislative Decree N° 1272 at the end of 2016. As such, its regulation is not free of loopholes (despite its short duration, the law was again modified on 2018) and already has been subject to different interpretations by different public administrations. In this paper, I aim to give an answer to some of the questions that have arisen in the short life of the “expiration” rule.